Integration of Self-diagnosis in Pascal Law Learning Using STEM Approach - Padliyyah, Siti Hannah; Suwarma, Irma Rahma; Jauhari, Agus (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Indonesia is ranked 56th out of 65 participating countries in the Program for International Student Assessment (PISA) based on data 2015. According to PISA results, the average science score of Indonesian students is 403, where this number is categorized as low. This is because students are still in the process of understanding and have not yet fully recognized the location of their mistakes. Students can diagnose the location of their mistakes through self-diagnosis activities. Self-diagnosis activities require the active role of students during the learning process. One approach that can increase the active role of students is STEM (Science Technology Engineering Mathematics). However, research at this time is still rarely found self-diagnosis activities that are applied to the STEM approach. Therefore, this research has the aim to find out the increase in mastery of physical concepts and self-diagnosis of students on the STEM learning approach to the theory of poscal law class XI High School.This study uses a One-Group pretest-posttest design with a sample of 30 ini 11th grade highschool from one schools in Bandung. . Based on the findings, there is an increase in mastery of concepts [<g> = 0.51] from pre-test to post-test. In self-diagnosis activities identified that there are differences in scores [z = 1.75; p = 0.9599] student assessment results of researchers and self-scoring results. Deeper self-diagnosis triggers a series of implicit steps that encourage them to rearrange their cognition by correcting the mistakes they make when solving problems. So that learning activities using the STEM approach that involves self-diagnosis activities can improve students' mastery of concepts.